2016
DOI: 10.5380/rf.v46i1.34991
|View full text |Cite
|
Sign up to set email alerts
|

Funcionalidade Ecológica De Sistemas Agroflorestais Biodiversos: Uso Da Serapilheira Como Indicador Da Recuperação De Áreas De Preservação Permanente

Abstract: ResumoAs recentes alterações na legislação brasileira incentivam a utilização de sistemas produtivos em áreas de preservação. Para avaliar a funcionalidade ecológica quanto ao aporte de biomassa e nutrientes, foi feito estudo de uma área de floresta e de quatro modelos de sistemas agroflorestais (SAFs) biodiversos e multiestratificados, com plantio de uma (solteira) a duas (casada) mudas por cova e com e sem consórcio de leguminosas, em Áreas de Preservação Permanente (APPs) no município de Paraty, RJ. A produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
0
8
0
3
Order By: Relevance
“…Alguns estudos foram desenvolvidos com serapilheira em áreas em processo de restauração florestal (GOMES et al, 2011;WANG'ONDU et al, 2014;SOUZA et al, 2016). Isso mostra que o aumento da deposição de serapilheira e nutrientes contribui positivamente para acelerar o desenvolvimento do ecossistema (MACHADO et al, 2015;LONDE et al, 2016).…”
unclassified
“…Alguns estudos foram desenvolvidos com serapilheira em áreas em processo de restauração florestal (GOMES et al, 2011;WANG'ONDU et al, 2014;SOUZA et al, 2016). Isso mostra que o aumento da deposição de serapilheira e nutrientes contribui positivamente para acelerar o desenvolvimento do ecossistema (MACHADO et al, 2015;LONDE et al, 2016).…”
unclassified
“…As previously observed, the Zea mays-E. grandis x E. urophylla-Acacia mangium-Brachiaria decumbens and Zea mays-E. grandis x E. urophylla agroforestry systems produce more litter than Brachiaria decumbens monoculture (FREITAS et al, 2013). However, when one compares deposition in secondary forests (SOUZA et al, 2016) or in native forests, such larger litter production is not often observed. This outcome suggests that native environments present higher litter yield values than consortium systems.…”
Section: Introductionmentioning
confidence: 53%
“…Litter nutrition content can be mainly influenced by the diversity (LIMA et al, 2010) and composition of the integrated crop-forestry system (SOUZA et al, 2016), as well as by vegetation structure and by abiotic factors such as light, temperature and rainfall, since all these factors can influence the biochemical and physiological processes (HOLANDA et al, 2017) due to differences in plants' anatomical features; soil humidity and temperature also influence the aforementioned variations (GUIMARÃES; CALIL, 2017). Eucalyptus globulus leaves have higher N, P, S, B and Mn content; fractions "thin branches" and "miscellany" recorded increased Fe and Mg content.…”
Section: Introductionmentioning
confidence: 99%
“…Higher litter production is observed in the dry season as a result of leaf abscission in response to water stress. However, Bianchin et al (2016), Souza et al (2016), and Villa et al (2016) pointed out that high litter production can occur during high rainfall periods, especially in dense ombrophilous forests.…”
Section: Litter Productionmentioning
confidence: 99%